(untitled) (TAMADDUN NURI JURNALI, 2024)
The article provides an analysis of the features of the economy of Uzbekistan in the second half of the 20th century, which indicates the reasons for the weak development of the economy of the republic. The article analyzes many statistics related to the state of the republic’s economy. All this provides reliable information about the economy of Uzbekistan in the "studied period."